The uncensored picture of Dorian Gray - Wilde, Oscar, 1854-1900 (Belknap Press of Harvard University Press, 2012)
This is the uncensored version of Oscar Wilde's 'The Picture of Dorian Gray'. The volume restores material, including instances of graphic homosexual content, removed by the novel's first editor.